DERADIKALISASI DALAM PENANGGULANGAN TINDAK PIDANA PERSPEKTIF UNDANG-UNDANG TERORISME DI INDONESIA - Samud Samud (Mahkamah : Jurnal Kajian Hukum Islam, 2021)
Deradicalization has a wide range of meanings, starting from matters of belief, legal handling, to correctionalization as an effort to change "radical" to "non-radical". But in simple terms, deradicalization can be understood as an effort to neutralize radicalism for those who are involved in acts of terrorism and their sympathizers, so that the terrorists or their sympathizers leave the violence. This definition of deradicalization is far from the tendency to corner certain religions. Because radicalism can grow in any religious community. Terror has been present and incarnated in our lives as a scourge, as a vicious virus and frightening monster which at times can not be expected to manifest "national and global catastrophes", including realizing human tragedies, castration of national dignity and the tragedy of human rights tragedy. (HAM). Human Rights (HAM) lost their existence and were deprived of their sanctity or finesse at the hands of terrorists who had created outrage in the form of social, political, cultural, and economic animalization